The Challenges of Learning Arabic Listening Skills Using Youtube as a Learning Tool - Azka, Lulu; Hafsoh, Ummi Nur; Ibrahim, Faishol Mahmoud Adam (Alsina : Journal of Arabic Studies, 2024)
This study investigates the challenges encountered in learning mahārat al-istimāʿ (listening skills) through using YouTube as a supplementary learning tool. Employing a quantitative approach with a survey design, the research gathered data on students’ experiences and perceptions regarding the integration of YouTube in Arabic listening instruction. The findings indicate several obstacles, such as rapid native speech, unclear dialogues, unfamiliar vocabulary, auditory processing difficulties, limited comprehension, and reduced concentration. The study also highlights the psychological effects and motivational responses associated with using this platform. Despite these challenges, YouTube demonstrates significant potential as a rich and accessible resource for enhancing listening skills. The study recommends improving content accessibility, applying stricter content selection, and integrating guided learning strategies to support a more effective and engaging learning environment.